Impact of funding influenza vaccination on coverage among Australian children: a national study using MedicineInsight, a large general practice database - Carla De Oliveira Bernardo; David Alejandro González-Chica; Nigel Stocks (Taylor & Francis Group, 2020)
Influenza contributes to morbidity and mortality worldwide. Children are at a higher risk of influenza-related complications and vaccination promotes direct protection and limits transmission. This study aimed to explore influenza vaccination coverage among children in Australian general practice from 2015 to 2018, and patterns in coverage before and after the implementation of state-funded immunization programs. Data from 196,520 'active' patients (3+ consultations in two consecutive years) aged <5 years from 542 Australian general practices were included (MedicineInsight database). Logistic regression models were used to identify associations between vaccination with patient and practice characteristics. The overall vaccination coverage increased more than five times from 2015 (3.9%) to 2018 (19.6%) and varied among states. Children attending practices located in the wealthiest areas were more likely to receive the vaccine and appeared to benefit most from the funding, as the increase in coverage from 2017 to 2018 was greater among them than those attending practices in the least advantaged areas (17 vs. 11 percentage points, respectively). This relationship was not evident when analyzing the patient's socioeconomic level. In conclusion, free influenza vaccinations increase coverage in at-risk populations. Promotional campaigns may be required to maintain higher coverage and target practices located in low-income areas.